A comparison of short-term outcomes between robot-assisted percutaneous vertebroplasty and manual percutaneous vertebroplasty in the treatment of osteoporotic thoracolumbar vertebral compression fractures - Lin, Hang; Li, Kun; Zhang, Zhibin; Haibier, Abuduwupuer; Abudurexiti, Tuerhongjiang (Frontiers in Surgery, 2025)
ObjectiveThe study aims to evaluate the clinical efficacy of robot-assisted vs. manual percutaneous vertebroplasty in managing osteoporotic thoracolumbar vertebral compression fractures.MethodsBased on the inclusion criteria, 111 patients who received unilateral percutaneous vertebroplasty (PVP) surgery at the Sixth Affiliated Hospital of Xinjiang Medical University between September and December 2023 were retrospectively reviewed. These patients were categorized into two groups according to surgical technique: the robotic-assisted group (n = 43) and the manual group (n = 68). The study compared demographic and clinical parameters between the groups, including age, sex, Body Mass Index(BMI), medical history (hypertension, diabetes, respiratory diseases, endocrine disorders), affected spinal segments, Visual Analogue Scale(VAS) and Oswestry Disability Index (ODI) scores, vertebral height restoration, Cobb angle, operative duration, cement volume, cement leakage, intraoperative blood loss, postoperative hospital stay, and total hospitalization costs.ResultsNo statistically significant differences were observed between the robotic-assisted and manual groups regarding age, gender, BMI, affected vertebral segments, medical history, preoperative/postoperative VAS and ODI scores, vertebral height restoration, Cobb angle, cement volume, total hospitalization costs, blood loss, or postoperative hospital stay (P > 0.05). However, significant differences were found between the two groups in both operative time and cement leakage rates (P < 0.05).ConclusionManual percutaneous vertebroplasty demonstrates superior operative time compared to robot-assisted percutaneous vertebroplasty. However, the robotic approach offers the advantage of reduced cement leakage, which enhances procedural safety and decreases postoperative complications to some degree. Furthermore, as surgeons gain proficiency with the robotic system, operative time can be further reduced. This technology warrants continued refinement and represents a promising direction for future development.